காலமும் - வெளியும் - காரைக்காலம்மையார் பிரபந்தங்கள் மற்றும் மணிவாசகரின் திருவாசகத்தை முன்னிறுத்திய உரையாடல் - Muhunthan, S. (நெய்தல், 2021)
The Dual entities like time and space play an important role in the development of theories related to physical and Meta physical Dogmas. The same applies to the fields of science, philosophy, and spirituality. In the Hindu tradition, Prabhanda’s of Karaikalammaiyar contains more ideas related to space. New ideas have been revealed in these, especially about Liminal Space' and Muppal. In Manivasaka's Thiruvasaka, the concepts of 'Time' are more elaborated than the concept of space. The Dimensional Theory of time, the Block Universe Theory of time and the Circular theory of Time are oriented in this way.
Keywords: Time; Space; Karaikalammaiyar; Metaphysical; Thiruvasaka